Transmission Accuracy Test Bed of Precision Gearbox with Small Modulus Gear - Qiao Yongqiang; Zheng Guoliang; Zhu Zhiyuan; Liu Xin; Chen Chao; Zhang Weiwei; Sun Zhiyang (Jixie chuandong)
The special transmission accuracy of detection test bed of gearbox is developed for the requirements of high- precision batch produced- gearbox,its mechanical structure has a modular design,which makes the test bed has the characteristics of high precision,easy to install,simple operation. By using the computer control,servo motor and precise angle measurement sensors,the test bed can control the circuits,the parameter detection of gearbox backlash,driving accuracy and efficiency can also be realized. By using the wavelet analysis in the single frequency filtering technology of its analysis software,the errors caused by all levels of the gearbox transmission chain can also be extracted by the test- bed.